2019
DOI: 10.1111/ncn3.12334
|View full text |Cite
|
Sign up to set email alerts
|

An atypical case of KMT2B‐related dystonia manifesting asterixis and effect of deep brain stimulation of the globus pallidus

Abstract: KMT2B-related dystonia (DYT-KMT2B) is a newly identified earlyonset generalized dystonia. 1 KMT2B encodes a lysine-specific histone methyltransferase 2B, which has a role in epigenetic modification of other genes, including those associated with dystonia (eg, THAP1 and TOR1A). DYT-KMT2B cases can exhibit characteristic facial features, microcephaly, short stature, and intellectual disability.The dystonia typically begins in the lower limbs and spreads to become generalized over a number of years, often with cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In total, 52 patients (23 in the study cohort and 29 patients in the published cohort) had GPiDBS inserted for medically intractable dystonia (Tables 1, 4 and Supplementary Table 8) (Coubes et al, 1999;Zech et al, 2016;Meyer et al, 2017;Zech et al, 2017;Zhao et al, 2018;Kawarai et al, 2018;Nerrant et al, 2018;Carecchio et al, 2019;Dafsari et al, 2019;Miyata et al, 2019;Mun et al, 2020). In our focused DBS cohort, the median postoperative follow-up was 2.0 years, with the longest follow-up of 22.0 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 52 patients (23 in the study cohort and 29 patients in the published cohort) had GPiDBS inserted for medically intractable dystonia (Tables 1, 4 and Supplementary Table 8) (Coubes et al, 1999;Zech et al, 2016;Meyer et al, 2017;Zech et al, 2017;Zhao et al, 2018;Kawarai et al, 2018;Nerrant et al, 2018;Carecchio et al, 2019;Dafsari et al, 2019;Miyata et al, 2019;Mun et al, 2020). In our focused DBS cohort, the median postoperative follow-up was 2.0 years, with the longest follow-up of 22.0 years.…”
Section: Discussionmentioning
confidence: 99%
“…Within the published cohort, eight publications reported a total of 31 subjects treated with DBS for KMT2B-dystonia (Zech et al, 2016;Meyer et al, 2017;Zech et al, 2017;Kawarai et al, 2018;Carecchio et al, 2019;Miyata et al, 2019;Cao et al, 2020;Mun et al, 2020) Overall, results were expressed mostly as "good or very good responses" and BFMDRS-M score changes were reported in 13 cases. (Supplementary Table 8)…”
Section: (F) Extended Kmt2b Cohort Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is suggested that DBS should be considered as a treatment approach in pharmacoresistent DYT-THAP1 early in childhood to prevent more severe symptoms, such as disabling motor development and quality of life decline, including emotional and social aspects, the results are missing. Additionally, bilateral GPi-DBS has been reported as a valuable therapeutic option for DYT-KMT2B, especially for regaining motor function and mobility, but less so for speech if significant speech difficulties are developed (5,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%